Allium Vegetables Intake and Risk of Breast Cancer: A Meta-Analysis - Jinhang Zhang; Jing Yang (Tehran University of Medical Sciences, 2022)
Abstract Background: Intake of allium vegetables may modify the risk of breast cancer. The aim of this study was to examine the association between allium vegetables intake and breast cancer risk via a meta-analysis. Methods: PubMed, Web of Knowledge, Scopus and Chinese National Knowledge Infrastructure (CNKI) were electronically searched up to June 2021 to identify relevant studies. We used random-effect models to calculate pooled risk estimates and their 95% confidence intervals (CIs) for risk of breast cancer with allium vegetables intake. Results: A total of 17 studies were included in this meta-analysis on the association of total allium vegetables, garlic and onion intake with breast cancer risk. The combined risk estimate of breast cancer for the highest vs lowest category of total allium vegetables, garlic and onion intake was 0.70 (95% CI: 0.49-0.91, P < 0.001), 0.77 (95% CI: 0.61-0.93, P = 0.016) and 0.75 (95% CI: 0.53-0.98, P < 0.001), respectively. A significant heterogeneity was found among studies for all three pooled analyses. Conclusion: High intake of allium vegetables may be protective against the development of breast cancer. Further well-designed prospective studies are needed to confirm the results.   Keywords: ; ; ; ;